Comprehensive analysis of spectral distribution of a large cohort of Chinese patients with non‐syndromic oculocutaneous albinism facilitates genetic diagnosis. (29th May 2019) - Zhong, Zilin; Gu, Li; Zheng, Xiujie; Ma, Nengjun; Wu, Zehua; Duan, Juan; Zhang, Jun; Chen, Jianjun
Abstract: Non‐syndromic oculocutaneous albinism (nsOCA) is a group of genetically heterogeneous autosomal recessive disorders with complete lack or decrease pigmentation in skin, hair, and eyes. TYR, OCA2, TYRP1, SLC45A2, SLC24A5, and LRMDA were reported to cause OCA1‐4 and OCA6‐7, respectively. By sequencing all the known nsOCA genes in 114 unrelated Chinese nsOCA patients combined with In silico analyses, splicing assay, and classification of variants according to the standards and guidelines of American College of Medical Genetics and Genomics, we detected seventy‐one different OCA‐causing variants separately in TYR, OCA2, SLC45A2, and SLC24A5, including thirty‐one novel variants (13 in TYR, 11 in OCA2, and 7 in SLC45A2 ). This study shows that OCA1 is the most common (75/114) and OCA2 ranks the second most common (16/114) in Chinese. 99 patients of our cohort were caused by variants of all the known nsOCA genes. Cutaneous phenotypes of OCA1, OCA2, and OCA4 patients were shown in this study. The second OCA6 case in China was identified here. These data expand the spectrum of OCA variants as well phenotype and facilitate clinical implement of Chinese OCA patients.